(3efJgi GdEOQGc aj JbGSje GdCadGcs - (3CHh eMeO YHO GdLHGQ Hf YHO GdLHGQ Hf eMeO GdKGHJj GdNQbj,J (B553 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdNdb hGdEHOGY hHYO aEf GdYde HCi eYdhe gh UaI TQa GYfi eYQaI CMhGd GdCadGc s
(3BNQgG (B:s
(3hef cSha GdbeQ jYQa ehVY GdbeQ HGdMbjbI ai adc GdHQhL Ydi eG SHb TQMg agPG eG CQOfGg ef HjGf CeQ GdcShajf adfNJe GdebGdI HgPG GdHGH s
(3GdebGdI GdChdis
(3HgG QShe hLOGhd adcjIs
(3cJHJ Hbde bdjd GdfbWs
(3HChdgG Jedc SfI (B703 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B47s
Keywords: (3Gdadcs